Scalar scenarios contributing to (g-2) mu with enhanced Yukawa couplings - Pires, C. A. D. S. [UNESP]; Silva, P. S. Rodrigues da [UNESP] (American Physical Soc, 2001)
In this work we address contributions from scalars to (g-2)μ. In order to explain the recently measured deviation by the BNL experiment on (g-2)μ, it is necessary that these scalars are either light or couple strongly with muons. Here we explore this last possibility. We show that a scalar with mass of the order of 102 GeV provides significant contribution to (g-2)μ if the Yukawa coupling is about 10-1. We suggest scenarios where this comes about naturally. ©2001 The American Physical Society.
Keywords: Electron; Elementary particle; Mass; Mathematical analysis; Measurement; Molecular interaction; Physics